Functional, biochemical and 3D studies of Mycobacterium tuberculosis protein peptides for an effective anti-tuberculosis vaccine (2014)
Tuberculosis (TB) is an air-born, transmissible disease, having an estimated 9.4 million new TB cases worldwide in 2009. Eventual control of this disease by developing a safe and efficient new vaccine able to detain its spread will have an enormous impact on public health policy. Selecting potential antigens to be included in a multi-epitope, minimal subunit-based, chemically-synthesized vaccine containing the minimum sequences needed for blocking mycobacterial interaction with host cells is a complex task due to the multiple mechanisms involved in M. tuberculosis infection and the mycobacterium's immune evasion mechanisms. Our methodology, described here takes into account a highly robust, specific, sensitive and functional approach to the search for potential epitopes to be included in an anti-TB vaccine; it has been based on identifying short mycobacterial protein fragments using synthetic peptides having high affinity interaction with alveolar epithelial cells (A549) and monocyte-derived macrophages (U937) which are able to block the microorganism's entry to target cells in in vitro assays. This manuscript presents a review of the results obtained with some of the MTB H37Rv proteins studied to date, aimed at using these high activity binding peptides (HABPs) as platforms to be included in a minimal subunit-based, multiepitope, chemically-synthesized, antituberculosis vaccine. © 2014 Informa Healthcare USA, Inc. All rights reserved: reproduction in whole or part not permitted.